Reseña de: Zeichmann, Christopher B. (ed.): Essential Essays for the Study of the Military in First-Century Palestine. Soldiers and the New Testament Context - González Salinero, Raúl (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2020)
Reseña de: Zeichmann, Christopher B. (ed.): Essential Essays for the Study of the Military in First-Century Palestine. Soldiers and the New Testament Context, Eugene (Oregon), Pickwick Publications, 2019, 151 pp., ISBN: 978-1-5326-5638-5.